The Digital Reception of A Hundred Thousand Billion Poems - Baillehache, Jonathan (Sens public)

(untitled) (Département des littératures de langue française, 2021)
Raymond Queneau’s Cent mille milliards de poèmes (CMMP) was first intended as a poetry writing “machine” (“machine à fabriquer des poèmes”). Queneau used the word “machine” in his preface to designate a tool designed to help the reader compose his/her own sonnets. Immediately after its publication in 1961, poetry smitten computer scientists and poets interested in computer science digitalized Queneau's book. All computer portings could generate poems automatically, thus transforming CMMP into a proto-text generator. The digital reception of CMMP made a composition tool into a machine. This article investigates the possible meanings of the word "machine" in the context of the adaptation of Queneau’s CMMP by D. Starynkevitch (1961) and Paul Braffort (1975).